Imaging Biological Pathways in Abdominal Aortic Aneurysms Using Positron Emission Tomography. Issue 5 (25th March 2021) - Bell, Michael; Gandhi, Richa; Shawer, Heba; Tsoumpas, Charalampos; Bailey, Marc A.
Abstract : Abdominal aortic aneurysm (AAA) is a focal dilation of the aorta associated with high mortality through rupture. Most of our understanding of the biology that drives AAA progression originates from surgical samples acquired in cases of elective open repair. These markers, which include macrophage infiltration and angiogenesis, have led to the exploration of novel radiopharmaceuticals to study AAA in preclinical models and human patients. Current clinical practice to detect AAA involves ultrasound-based screening and surveillance. Although ultrasound is cheap and without radiation risk, aortic diameter does not predict the heterogenous growth of AAA between patients. Positron emission tomography takes advantage of novel radiolabeled markers of disease to track biological changes. In human trials, the role of 2-[ 18 F]-flurordeoxyglucose in detecting aneurysm growth and outcome is still debated, whereas sodium [ 18 F]-fluoride has been shown to predict AAA growth and clinical outcome through highlighting microcalcification. Murine studies have been used to assess the suitability of radiotracers detecting inflammation, angiogenesis, and proliferation. However, in the absence of human data, the clinical suitability and applicability of these tracers remain speculative. This review examines how markers of AAA change over time and the ability of positron emission tomography to track these changes and discusses the radiopharmaceuticals that could have an application in stratifying AAA subjects.